Employee engagement driving program: Efforts to optimize employee performance - Pundani Eki Pratiwi; Siti Nuzulia; Bogy Febriatmoko; Pradipta Christy Pratiwi (University of Merdeka Malang, 2023)
A company that is undergoing a transition period often faces employee work behavior that does not support the achievement of company goals. In this service partner, employees show minimal work behavior, lack of innovation, lack of energy, and lack of initiative. These emerging behaviors illustrate disengagement behavior that affects company performance. This condition makes it difficult for companies to carry out existing business strategies. The company needs a way to increase employee engagement in the process of implementing company strategies that support the achievement of company goals/performance. To overcome these problems, the service team uses the